2005
DOI: 10.1128/jvi.79.6.3448-3458.2005
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Localization of Japanese Encephalitis Virus Core Protein Enhances Viral Replication

Abstract: Japanese encephalitis virus (JEV) belongs to the genus Flavivirus within the family Flaviviridae. Members of the genus Flavivirus are predominantly arthropodborne viruses and frequently cause significant morbidity and mortality in mammals and birds (6). JEV is distributed in the south and southeast regions of Asia and kept in a zoonotic transmission cycle between pigs or birds and mosquitoes (6,50,57). JEV spreads to dead-end hosts, including humans, through the bite of JEVinfected mosquitoes and causes infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
151
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(161 citation statements)
references
References 60 publications
10
151
0
Order By: Relevance
“…This feature appears to be conserved among flaviviruses, as other investigators have detected C proteins of Kunjin virus, West Nile virus and Japanese encephalitis virus (JEV) in both the cytoplasm and nuclei of infected mammalian cells (Westaway et al, 1997;Mori et al, 2005;Oh et al, 2006). Three stretches of Arg/Lys-rich sequence in the dengue virus C protein have been proposed to serve as nuclear-localization signals (NLSs): KKAR, located at aa 6-9; KKSK, located at aa 73-76; and the bipartite sequence RKEIGRMLNILNRRRR, located at aa 85-100 (Bulich & Aaskov, 1992).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…This feature appears to be conserved among flaviviruses, as other investigators have detected C proteins of Kunjin virus, West Nile virus and Japanese encephalitis virus (JEV) in both the cytoplasm and nuclei of infected mammalian cells (Westaway et al, 1997;Mori et al, 2005;Oh et al, 2006). Three stretches of Arg/Lys-rich sequence in the dengue virus C protein have been proposed to serve as nuclear-localization signals (NLSs): KKAR, located at aa 6-9; KKSK, located at aa 73-76; and the bipartite sequence RKEIGRMLNILNRRRR, located at aa 85-100 (Bulich & Aaskov, 1992).…”
Section: Introductionmentioning
confidence: 78%
“…Kinetics of C protein localization to nuclei and nucleoli of dengue virus-infected cells Several investigators have reported different patterns of dengue virus and other flavivirus C protein nuclear localization, or lack thereof, in many cell lines, which may reflect cellular differences and methodological variations (Tadano et al, 1989;Bulich & Aaskov, 1992;Westaway et al, 1997;Ng et al, 2001;Wang et al, 2002;Mori et al, 2005;Oh et al, 2006). To affirm the phenomenon in this study, subcellular localization of dengue virus C protein was assessed during infection of two mammalian cell lines (PS and Vero) and a mosquito cell line (C6/36) with a dengue serotype 2 virus, strain 16681, by using indirect IFA.…”
Section: Resultsmentioning
confidence: 99%
“…The C protein localizes to three distinct cellular compartments: the ER membrane and lipid droplets in the cytoplasm, as well as the nucleus (specifically the nucleolus) (Bhuvanakantham et al, 2010;Bulich & Aaskov, 1992;Colpitts et al, 2011; Martins et al, 2012;Mori et al, 2005;Samsa et al, 2009; Westaway et al, 1997). The primary role of the C protein in the flavivirus life cycle is in the assembly of the nucleocapsid and its incorporation into nascent virions, whilst other functions of C, including those performed in the nucleus, are less explored.…”
Section: Proteinmentioning
confidence: 99%
“…Phosphorylation of WNV C has conversely been shown to promote nuclear localization and thus removes the protein from sites of genomic RNA interaction (Bhuvanakantham et al, 2010). The Kunjin virus (KUNV; a naturally attenuated strain of WNV) and DENV C structures place a-1 in different orientations; thus, it is hypothesized that this helix rotates in order to change the position of the flexible N terminus for optimal RNA interaction (Dokland et al, 2004;Ma et al, 2004).The C protein localizes to three distinct cellular compartments: the ER membrane and lipid droplets in the cytoplasm, as well as the nucleus (specifically the nucleolus) (Bhuvanakantham et al, 2010;Bulich & Aaskov, 1992;Colpitts et al, 2011; Martins et al, 2012;Mori et al, 2005;Samsa et al, 2009; Westaway et al, 1997). The primary role of the C protein in the flavivirus life cycle is in the assembly of the nucleocapsid and its incorporation into nascent virions, whilst other functions of C, including those performed in the nucleus, are less explored.…”
mentioning
confidence: 99%
“…Studies with Japanese encephalitis virus, a related flavivirus, indicate that nuclear localization of C is important for virus replication and neuroinvasiveness, but interestingly not for neurovirulence (Mori et al, 2005). The WNV C protein has also been implicated as a pathogenic determinant; expression of WNV C in the absence of other viral proteins has been reported to cause apoptosis in neurons both in vitro and in vivo (Yang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%